The population status and maize crop-raiding activities of Papio anubis and Chlorocebus pygerythrus in the Abala Abaya forest, located in southern Ethiopia - Senait Samuel; Wondimagegnehu Tekalign (Discover Applied Sciences)
Abstract Species and subspecies of primates occur in different parts of Ethiopia, and some of them are successful crop raiders. We conducted a study on the population status and maize crop-raiding activities of Anubis baboons (Papio anubis) and Vervet monkeys (Chlorocebus pygerythrus) within a mosaic forest located in southern Ethiopia. Data was gathered using mixed-method approaches. Fourteen transects were employed to directly observe the status of the primate population. Additionally, a questionnaire survey was conducted to collect information regarding the maize crop-raiding activities of the primates. Categorical variables were analyzed using the a one-way analysis of variance (ANOVA). There was no significant relationship between Chlorocebus pygerythrus and Papio anubis population sizes during the wet and dry seasons in either habitat type. Most individuals from the two species were recorded at the sub-adult stage in both habitats. The Papio anubis recorded the most significant maize crop damage during the ripened stage, while the Chlorocebus pygerythrus experienced its highest maize crop damage at the flowering stage. The least damage caused by both species was at the seedling stage. The yearly loss of the maize harvest caused by the primates was estimated to be around eight quintals, or 800 kg, valued at approximately $296. Surveillance and hazing by humans were the most popular methods to mitigate loss of crops to primates. The results of our study indicate that the food security of the examined farmers is jeopardized by crop-raiding primates, and this outcome is vital for formulating management plans and executing effective conservation strategies.